2018
DOI: 10.1016/j.chom.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Antibiotic-Driven Dysbiosis Leads to Dysregulated Vaccine Immune Responses in Mice

Abstract: Antibody-mediated responses play a critical role in vaccine-mediated immunity. However, for reasons that are poorly understood, these responses are highly variable between individuals. Using a mouse model, we report that antibiotic-driven intestinal dysbiosis, specifically in early life, leads to significantly impaired antibody responses to five different adjuvanted and live vaccines. Restoration of the commensal microbiota following antibiotic exposure rescues these impaired responses. In contrast, antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
165
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(176 citation statements)
references
References 51 publications
4
165
2
Order By: Relevance
“…Furthermore, it has been indicated that early-life gut microbiota dysbiosis damages vaccine immune responses [49,50]. In this study, we found that early-life intervention with FMT-CS can reduce the risk of gut microbiota dysbiosis, as well as improve the antibody levels of M.hyo and PCV2.…”
Section: Early-life Intervention With Fmt-cs Promotes the Developmentmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, it has been indicated that early-life gut microbiota dysbiosis damages vaccine immune responses [49,50]. In this study, we found that early-life intervention with FMT-CS can reduce the risk of gut microbiota dysbiosis, as well as improve the antibody levels of M.hyo and PCV2.…”
Section: Early-life Intervention With Fmt-cs Promotes the Developmentmentioning
confidence: 60%
“…Potential pathogens, such as Fusobacteriaceae, Lachnospiraceae, Enterobacteriaceae, and Akkermansia, were significantly decreased in treated piglets, indicating a lower occurrence rate of intestinal dysbiosis [50]. The above results suggest that early-life intervention with FMT-CS increases the relative abundance of beneficial bacteria, while decreases that of opportunistic pathogens.…”
Section: Early Intervention With Fmt-cs Increases Beneficial Bacteriamentioning
confidence: 70%
“…The application of radiomics to PDAC has generated optimism, but it is also challenging because of nonspecific clinical presentation and subtle imaging findings. Previous studies on the application of radiomics to PDAC have focused on prognostic assessments and differential diagnosis [40][41][42][43]. The current study used radiomics features of the entire 3D volume to assess preoperative LN status in patients with PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic treatment-induced dysbiosis can have widereaching effects, for example on inflammation, infection and responses to vaccination [70][71][72]. Antibiotics have been shown to affect SCFA-producing bacteria causing a decrease in SCFA abundance [73,74].…”
Section: Effect Of Commensal Metabolites On Host Immune Functionmentioning
confidence: 99%